1984
DOI: 10.1152/ajpendo.1984.247.5.e657
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance of denervated rat muscle: a model for impaired receptor-function coupling

Abstract: The effect of short-term denervation on the response to insulin was studied in isolated rat soleus and extensor digitorum longus (EDL) muscles 6 and 24 h after severing one sciatic nerve. Impaired insulin sensitivity and response occurred within 6 h postdenervation in solei. After 24 h, EDL of fed and fasted rats and solei of fed rats showed no stimulation of glycogen synthesis even with supraphysiological doses, whereas solei of fasted rats showed markedly decreased sensitivity and response to insulin. Insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 26 publications
6
57
0
1
Order By: Relevance
“…The increase in basal glucose utilization observed in the present study may be an effect of denervation as a comparable effect has been described in rat diaphragm after denervation [23,24]. The in vivo effect of denervation (24 h) to decrease substantially insulin-induced glycogen synthesis in soleus [25] and diaphragm [24] was not seen in vitro in the present study. Factors in addition to denervation per se may therefore be involved in vivo.…”
Section: Resultssupporting
confidence: 81%
“…The increase in basal glucose utilization observed in the present study may be an effect of denervation as a comparable effect has been described in rat diaphragm after denervation [23,24]. The in vivo effect of denervation (24 h) to decrease substantially insulin-induced glycogen synthesis in soleus [25] and diaphragm [24] was not seen in vitro in the present study. Factors in addition to denervation per se may therefore be involved in vivo.…”
Section: Resultssupporting
confidence: 81%
“…The glycogen was precipitated by the sequential addition of 100 l of 2 M Na 2 SO 4 and 1 ml EtOH at Ϫ 20 Њ C for 16 h. The pellet was collected and washed twice with 1 ml KOH and 1 ml of EtOH and hydrolyzed in 0.5 ml 4 N H 2 SO 4 at 100 Њ C for 1 h. The solution was neutralized and glucose determined by the glucose oxidase method (22).…”
Section: St Louis Mo] and Triglycerides/gb [Boehringer Mannheim])mentioning
confidence: 99%
“…16 Electrical stimulation has been shown to improve muscle ®ber structure and function. 15,17,18 In animal models, investigators have reported the deleterious e ect of denervation on postreceptor insulin action, 19 exercise-induced glucose uptake, 20 insulin receptor binding, 21,22 receptor phosphorylation, 21 and the glucose transporter protein (GLUT-4). 23 ± 25 In a recent study, 26 individuals with tetraplegia were found to have a marked reduction in whole body glucose transport that appeared to be due to a proportional reduction in muscle mass.…”
Section: Determinants Of Insulin Resistancementioning
confidence: 99%